Annual Plant Reviews Online 2019
DOI: 10.1002/9781119312994.apr0681
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for Developing Salt‐tolerant Wheat and Barley Varieties

Abstract: Salinity is a major constraint limiting crop yields around the world. While considerable research to understand and enhance the salinity tolerance of plants has occurred, few commercially available salt‐tolerant bread wheat ( Triticum aestivum ), durum wheat ( Triticum durum ), or barley ( Hordeum vulgare ) varieties have been developed for farmers. This lack of salt‐tolerant varieties is despite all publications highlighting issues around… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 180 publications
0
7
0
Order By: Relevance
“…To date, a limited number of studies have been conducted to identify QTL linked with shoot ion-independent tolerance and/ or Claccumulation in bread wheat, with the majority of studies focusing on the identification of QTL for shoot ion accumulation (mostly Na + exclusion and K + accumulation) (Dubcovsky et al 1996;Ma et al 2007;Genc et al 2010Genc et al , 2013Díaz De León et al 2011;Oyiga et al 2018;Asif et al 2019). Shoot ion-independent tolerance is an important tolerance mechanism and helps plants in maintaining tissue expansion and tillering during the initial phase of salt stress before salt accumulates to toxic levels in the shoot (Roy et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, a limited number of studies have been conducted to identify QTL linked with shoot ion-independent tolerance and/ or Claccumulation in bread wheat, with the majority of studies focusing on the identification of QTL for shoot ion accumulation (mostly Na + exclusion and K + accumulation) (Dubcovsky et al 1996;Ma et al 2007;Genc et al 2010Genc et al , 2013Díaz De León et al 2011;Oyiga et al 2018;Asif et al 2019). Shoot ion-independent tolerance is an important tolerance mechanism and helps plants in maintaining tissue expansion and tillering during the initial phase of salt stress before salt accumulates to toxic levels in the shoot (Roy et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…QTL mapping is a valuable tool for studying complex polygenic traits like salinity tolerance in various crops (Ortiz 1998;Ruttan 1999;Roy et al 2011). QTL for salinity tolerance have been identified in a large number of plant species including bread wheat (Asif et al 2019); however, limited success has been made so far regarding the identification of candidate genes and development of new salt tolerant wheat cultivars (Gilliham et al 2017;Asif et al 2019). Hence, more studies are needed to identify and understand salt tolerance mechanisms and the underlying genes responsible for such traits.…”
Section: Introductionmentioning
confidence: 99%
“…Although genes that encode Cl − channels or transporters have been identified (see Colmenero-Flores et al 2007;Barbier-Brygoo et al 2011;De Angeli et al 2013Henderson et al 2014Herdean et al 2016;Li et al 2016Li et al , 2017Geilfus 2018Geilfus , 2019Wu and Li 2019 for examples), the genes/proteins specifically involved in Cl − salinity tolerance in cereals remain unknown. To date, few studies have reported QTL for plant Cl − accumulation in bread wheat under salinity (Asif et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the previous studies on salinity tolerance in crops have focused on the role of Na + and K + and ignored Cl − (Asif et al., 2019). Although saline soils contain both Na + and Cl − ions, not much is known about physiological and genetic control tolerance mechanisms related to Cl − toxicity compared with Na + toxicity (Genc et al., 2014; Teakle & Tyerman, 2010).…”
Section: Discussionmentioning
confidence: 99%